Idiopathic Hypoparathyroidism With Papillary Thyroid Carcinoma in a Young Male: A Rare Case Report - Chen, Wenjie; Chen, Liyun; Wei, Tao; Li, Zhihui; Lei, Jianyong; Zhu, Jingqiang (Frontiers in Endocrinology, 2020)
Background Idiopathic hypoparathyroidism (IHP) is a rare disorder that is diagnosed by excluding other possible etiologies. Thyroid surgery causes approximately 14-60%of all cases of hypoparathyroidism; of these, surgery for papillary thyroid carcinoma (PTC) is the most common reason. Here, we report an extremely rare case of IHP combined with PTC. Case presentation A 22-year-old man presented with a history of uncontrollable extremity and facial numbness, spasm and twitch lasting for nine years. He had been misdiagnosed with epilepsy and gained no relief from antiepileptic therapy. The laboratory evaluation revealed reduced parathyroid hormone eand serum calcium and elevated inorganic phosphorus. After considering IHP, ultrasound detected a solid hypoechoic and irregularly shaped nodule 13×8×9 mm in size in the upper pole of the right thyroid gland, and fine-needle aspiration biopsy indicated PTC. Then, the patient underwent surgical treatment and radioactive iodine ablation. The long-term treatment strategy consisted of oral levothyroxine for thyroid-stimulating hormone inhibition and oral calcium and vitamin D supplements for hypocalcemia control. Conclusion We report a rare case of IHP combined with PTC in a 22-year-old male. Some experiences and lessons from our treatment procedure merit discussion, and we hope that our report can serve as a reference for the diagnosis and treatment of similar patients in the future.